Whose bread I don’t eat, his song I don’t sing?: MPs’ outside earnings and dissenting voting behaviour - Mai, Philipp (Party politics, 2020)
The question whether politicians’ outside earnings affect their legislative behaviour is part of a lively debate about the quality of representative democracy. However, moonlighting effects on vote defections by members of parliament (MPs) have remained underexposed yet. Based on Competing Principals Theory, it is argued that, owing to a higher degree of career-related independence, MPs with high outside earnings can be less effectively disciplined by their party and, therefore, show higher probabilities to vote against the party line. This proposition is tested quantitatively using logistic panel regressions against a new dataset of more than 115,000 individual votes in the German Bundestag (2013-2017). Empirically, the results corroborate the theoretical expectations and are robust against different specifications. The findings have important implications for our understanding of the link between politicians’ career paths and their political behaviour.